Uncoupling neocortical neuron fate and migration via a Let-7–RBX2 axis - Steven C. Decker; Keiko Hino; Anna La Torre; Sergi Simó (Proceedings of the National Academy of Sciences, 2026)
Throughout the central nervous system, the fate and migration of projection neurons (PNs) are tightly coordinated to ensure that specific neuronal fates settle in precise spatial locations. This is particularly evident in the mammalian neocortex, where early-born PNs predominantly remain in the deeper layers of the cortical plate, whereas later-born neurons localize more superficially. However, it remains unclear whether neuronal fate acquisition directly primes the molecular mechanisms driving PN migration and positioning, or on the contrary fate and positioning are regulated independently. MicroRNAs have emerged as key regulators of cell fate determination in the neocortex. Among them, let-7 is known to influence neural progenitor competence and promote the neurogenesis of late-born PNs. Here, we show that let-7 also regulates PN migration and positioning by targeting RBX2, a core component of the E3 ubiquitin ligase CRL5, which has been previously shown to inhibit neuron migration by terminating the Reelin/DAB1 signaling pathway. Let-7 directly binds to a conserved motif in the 3′UTR of RBX2, reducing its translation and thereby diminishing CRL5 activity. Importantly, restoring RBX2 levels in the context of let-7 overexpression rescues the positioning of PNs without altering let-7-induced effects on neuronal fate. Furthermore, we demonstrate that let-7 enhances PN migration by increasing locomotion speed and prolonging migratory activity. Together, these findings reveal that let-7 coordinates neuronal fate specification and migration via distinct molecular pathways, ensuring the proper laminar positioning of late-born PNs in the neocortex.